Human-Like Eukaryotic Translation Initiation Factor 3 from Neurospora crassa - Smith, M. Duane; Gu, Yu; Querol-Audí, Jordi; Vogan, Jacob M.; Nitido, Adam; Cate, Jamie H. D. (PLOS ONE, 2013)
Eukaryotic translation initiation factor 3 (eIF3) is a key regulator of translation initiation, but its in vivo assembly and molecular functions remain unclear. Here we show that eIF3 from Neurospora crassa is structurally and compositionally similar to human eIF3. N. crassa eIF3 forms a stable 12-subunit complex linked genetically and biochemically to the 13th subunit, eIF3j, which in humans modulates mRNA start codon selection. Based on N. crassa genetic analysis, most subunits in eIF3 are essential. Subunits that can be deleted (e, h, k and l) map to the right side of the eIF3 complex, suggesting that they may coordinately regulate eIF3 function. Consistent with this model, subunits eIF3k and eIF3l are incorporated into the eIF3 complex as a pair, and their insertion depends on the presence of subunit eIF3h, a key regulator of vertebrate development. Comparisons to other eIF3 complexes suggest that eIF3 assembles around an eIF3a and eIF3c dimer, which may explain the coordinated regulation of human eIF3 levels. Taken together, these results show that Neurospora crassa eIF3 provides a tractable system for probing the structure and function of human-like eIF3 in the context of living cells.